2018
DOI: 10.1515/jpem-2017-0285
|View full text |Cite
|
Sign up to set email alerts
|

Association of cord blood ghrelin, leptin and insulin concentrations in term newborns with anthropometric parameters at birth

Abstract: In summary, it was confirmed that cord blood ghrelin, leptin and insulin correlate with anthropometric parameters at birth. This study showed a negative correlation of AG with anthropometric parameters, which may emphasize that this hormone is an indicator of growth restriction. This is in contrast to cord leptin and insulin, which are more connected with overgrowth. Taking all the results into consideration, the metabolic status of the fetus and newborn is an essential component in understanding the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…There have been only a few studies evaluating ghrelin concentrations in preterm infants, and studies in SGA preterm infants are limited [23,[27][28][29]. Our data revealed a negative association between cord blood ghrelin levels and birth weight and gestational age in preterm newborns.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…There have been only a few studies evaluating ghrelin concentrations in preterm infants, and studies in SGA preterm infants are limited [23,[27][28][29]. Our data revealed a negative association between cord blood ghrelin levels and birth weight and gestational age in preterm newborns.…”
Section: Discussionmentioning
confidence: 54%
“…The differences in cord blood concentrations between SGA and AGA infants, when exposed to hypertension, suggest a probable role of adipokines in fetal growth. There are reports of an association of adipokine levels and fetal growth in the literature [23,24]. Previous studies have shown that these hormones may have an effect on anthropometric growth parameters [23,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When antibodies against ghrelin are administered to rats during pregnancy, the size and weight of the rat litter is reduced compared to controls 33 . Similarly, babies born SGA have lower levels of cord ghrelin than normal‐sized babies 34,35 . Our previous work reports reduced circulating ghrelin during VSG pregnancy 36 .…”
Section: Introductionmentioning
confidence: 89%
“…33 Similarly, babies born SGA have lower levels of cord ghrelin than normal-sized babies. 34,35 Our previous work reports reduced circulating ghrelin during VSG pregnancy. 36 The effect of low endogenous ghrelin on the offspring of VSG pregnancy has not been addressed.…”
Section: Introductionmentioning
confidence: 97%